The Role of the Press in Disseminating Ideas and Intellectual Thoughts During the National Movement - Nababan, Dora Irene; Pangaribuan, Juli; Tampubolon, Jimmy Saputra (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2024)
The role of the press in disseminating ideas and thoughts plays an important role in forming public awareness, mobilizing national movements, and influencing social change. This article examines the development of the press during the national movement, its function in spreading thoughts and ideas, and its impact in mobilizing society in the struggle for independence. This research uses a historical research approach by collecting and analyzing various relevant sources such as books, journals and historical documents related to the role of the media in the Indonesian national movement. The results of this research provide insight into the important role of the press in disseminating ideas and intellectual ideas, as well as their impact on social changes that occurred during the national movement.